Development of agent recommendation system of virtual university based on JADE - Glybovets, M.M.; Konyushenko, O.V. (PROBLEMS IN PROGRAMMING, 2017)
The paper presents a model of agent-based recommendation system (RS), which will operate in a framework of the virtual university and describes its multi-agent implementation based on JADE. Author grounds the choice of RS type (item-based collaborative filtering systems), algorithms that are used in various steps of generating recommendations and itemizes the role and behavior of agents.